A super-salt of tungsten disulfide-h-bn self-lubricating wear-resistant composite material

CN123003184APending Publication Date: 2026-10-30LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611163788.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,该材料无法通过自润滑特性使熔盐在其表面抗结焦与自脱落,使其应用具有局限性

Benefits of technology

1、本发明通过对h-BN的空位氧掺杂调节了h-BN的表面缺陷浓度,氧原子取代硼或氮原子进入空位后,能够有效调控h-BN的表面能与电子结构,在保持h-BN本身高导热、高温稳定特性的同时,降低h-BN的表面能,为实现熔融钠盐的非润湿特性提供了结构基础;另一方面,空位氧掺杂后氮化硼的化学活性提升,有利于后续的羟基化改性、功能基团接枝以及与WS2之间发生共价插层反应。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003184A_ABST
    Figure CN123003184A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of tungsten disulfide-h-BN self-lubricating wear-resistant composite of super-salt, the composite material has two-dimensional composite " sandwich intercalation " structure, is obtained by WS2 and the hydroxyl modification of h-BN, vacancy defect regulation and covalent intercalation method.The hybrid structure with interlayer van der waals force weakening, defect energy level controllable hybrid structure is constructed, the performance synergy of hybrid structure is used, realizes the low friction performance in the temperature range of room temperature to 1000 DEG C, simultaneously obtains stable non-wetting characteristics to molten sodium salt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic non-metallic composite material preparation and high-temperature surface superwetting protective materials, and particularly to a superhydrophobic tungsten disulfide (WS2)-h-BN self-lubricating wear-resistant composite material. Background Technology

[0002] my country's Xinjiang Uygur Autonomous Region has abundant reserves of high-alkali coal, mainly distributed in the Junggar Basin and the Jungdong region. The sodium content of alkali metal in this coal is much higher than that of conventional coal. During the combustion process in power plant boilers, the sodium-containing substances in the coal will decompose upon heating to form molten sodium salts, which are very easy to adhere to the surface of the boiler water-cooled walls, superheaters and other heating surfaces, thereby inducing coking and corrosion problems. This will not only reduce the heat exchange efficiency of the boiler, but also cause corrosion and damage to the heating surface pipes, seriously threatening the safe and stable operation of the boiler.

[0003] Currently, common protective methods involve spraying ordinary ceramic or metal-based coatings onto the heated surfaces. However, these materials generally suffer from poor high-temperature self-lubrication, insufficient wear resistance, and weak resistance to molten sodium salt wetting. After long-term operation, problems such as molten sodium salt adhesion and coking, and coating wear and peeling still occur, failing to meet the protection requirements for long-term stable operation of boilers using high-alkali coal. Patent CN 115050490 B describes adding a catalyst-containing thermosetting resin monomer or oligomer precursor solution to the pores of graphite, followed by high-temperature carbonization to form carbon nanostructures, thereby improving the barrier properties of graphite against molten salts and molten metals. However, its carbon nanostructures are mainly used to seal the pores inside the graphite, lacking control over the high-temperature super-wetting and wear resistance of the material surface, and cannot effectively solve the problems of reducing atmosphere generated during combustion and fly ash wear during soot blowing. Furthermore, the vacuum and inert atmosphere environment during carbonization requires high-quality production conditions, making it unsuitable for long-term protection of boiler heated surfaces. Patent CN117286384 B proposes a bonding layer material resistant to molten salt hot corrosion. This material resists molten salt hot corrosion by generating a mixed oxide layer of Zr₂O₃, Al₂O₃, and Cr₂O₃ through an AlCoCrNiZr high-entropy alloy during oxidation and hot corrosion. However, this material cannot prevent molten salt from coking or detaching from its surface through self-lubricating properties, thus limiting its application.

[0004] Therefore, developing a protective composite material that can combine low friction and wear resistance in high-temperature environments with excellent non-wetting properties against molten salt is key to solving the problems of molten sodium salt adhesion, wetting, coking, and corrosion during the combustion of high-alkali coal. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a high-performance superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material.

[0006] To address the aforementioned problems, the present invention provides a superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material, characterized in that: the composite material has a two-dimensional composite "sandwich intercalation" structure, which is prepared by hydroxyl modification of WS2 and h-BN, vacancy defect regulation, and covalent intercalation.

[0007] The contact angle of the molten salt on the surface of the composite material is >150°, and the coefficient of friction is 0.02~0.3 in the temperature range of room temperature to 1000℃.

[0008] The molten salt is one or more of sodium chloride, sodium sulfate, sodium carbonate, and sodium bicarbonate, with a melting point range of 300~1000℃.

[0009] The WS2 is a hexagonal plate-like tungsten sulfide with a particle size controlled at 0.5~1 μm and a specific surface area controlled at 62~98 cm². 2 / g, purity ≥99.9%; the h-BN is hexagonal plate-like hexagonal boron nitride with a particle size controlled at 25~50 μm and a density of 2.1~2.29 g / cm³. 3 The boron content is >43.6%.

[0010] The preparation method of the superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material as described above includes the following steps: S1. WS2 powder and hydroxyl modifier are sequentially added to an ultrapure aqueous solution in a mass ratio of 0.3:0.01~0.1:1. The solution is stirred at 800~1000 r / min for 12~24 h to obtain a WS2 hydroxylated modified solution. The WS2 hydroxylated modified solution is then vacuum filtered and dried to obtain hydroxylated modified WS2 powder. S2. h-BN powder is placed in a muffle furnace for high-temperature oxygen doping. After the muffle furnace cools naturally, the vacancy-defect oxygen-doped h-BN powder is collected. The vacancy-defect oxygen-doped h-BN powder and hydroxyl modifier are added sequentially to an ultrapure aqueous solution at a mass ratio of 0.1:0.02~0.1:1. The solution is stirred at 800~1000 r / min for 12~24 h to obtain an h-BN hydroxylation-modified solution. The h-BN hydroxylation-modified solution is then vacuum filtered and dried to obtain hydroxylation-modified h-BN powder. S3. The hydroxylated modified WS2 powder, the hydroxylated modified h-BN powder, and the covalent intercalation solvent are added sequentially to a ball mill jar at a mass ratio of 0.6~0.75:1:0.01, and wet ball milling is performed in a high-energy ball mill to obtain a mixed powder. The mixed powder is then vacuum filtered and dried to obtain the WS2-h-BN self-lubricating wear-resistant composite material.

[0011] The hydroxyl modifier in steps S1 and S2 refers to one of H2O2, NaOH, and PFDTS.

[0012] The drying conditions in step S1 refer to a temperature of 90°C and a time of 10 hours.

[0013] In step S2, the mass ratio of h-BN powder to WS2 powder is 1:0.6~0.75.

[0014] In step S2, high-temperature oxygen doping refers to a heating rate of 3~5 ℃ / min for the muffle furnace, a set temperature of 600~850℃, and a holding time of 1.5~2 h.

[0015] The drying conditions in step S2 refer to a temperature of 70°C and a time of 16 hours.

[0016] The covalent intercalation solvent in step S3 is one or both of APTES and KH560.

[0017] The conditions for wet ball milling in step S3 are as follows: the solvent is anhydrous ethanol, the ball milling speed is 800~1200 rpm, the ball-to-material mass ratio is 5:1, the mass ratio of anhydrous ethanol to raw material is (1.5~2):1, and the ball milling time is 24~36 h.

[0018] The drying conditions in step S3 are a temperature of 90°C and a time of 2.5 h.

[0019] Compared with the prior art, the present invention has the following advantages: 1. This invention adjusts the surface defect concentration of h-BN by doping with vacant oxygen. After oxygen atoms replace boron or nitrogen atoms in the vacancy, the surface energy and electronic structure of h-BN can be effectively controlled. While maintaining the high thermal conductivity and high temperature stability of h-BN itself, the surface energy of h-BN is reduced, providing a structural basis for realizing the non-wetting properties of molten sodium salt. On the other hand, the chemical activity of boron nitride is enhanced after vacant oxygen doping, which is beneficial to subsequent hydroxylation modification, functional group grafting, and covalent intercalation reaction with WS2.

[0020] 2. This invention overcomes the inherent agglomeration problem of WS2 and h-BN by hydroxylating WS2 and high-temperature oxygen-doped h-BN, improving their dispersion uniformity in aqueous solutions. This provides numerous reactive sites for subsequent covalent intercalation, ensuring uniform and stable intercalation assembly and avoiding phase separation caused by WS2 and h-BN agglomeration, which would affect the overall uniformity of the material's properties. Furthermore, the hydroxyl modification process does not destroy the hexagonal plate-like crystal structure of WS2 and h-BN, preserving their excellent resistance to chlorine corrosion, high-temperature self-lubrication, and thermal stability, thus providing stable wear resistance.

[0021] 3. In the intercalation assembly process, WS2 with hydroxyl groups and h-BN can promote the bonding reaction between hydroxyl groups and covalent intercalation solvent functional groups, ensuring the uniformity of the structure of WS2 and h-BN during the intercalation assembly process, and improving the interfacial intercalation bonding strength, effectively avoiding the problem of peeling failure during long-term friction caused by weak interfacial bonding.

[0022] 4. This invention increases the interlayer spacing between WS2 and h-BN through hydroxylation modification, vacancy defect regulation and covalent intercalation assembly of WS2-h-BN. The increased interlayer spacing reduces the interlayer van der Waals force and friction coefficient between WS2 and h-BN, thereby giving it stronger self-lubricating properties and low surface energy properties.

[0023] 5. Through covalent intercalation assembly of WS2-h-BN, the WS2-h-BN self-lubricating wear-resistant composite material prepared by this invention fully combines the excellent high-temperature self-lubricating properties of WS2 with the high thermal conductivity, high-temperature stability, and corrosion resistance of h-BN. Through the synergistic advantages of the structure and performance of WS2 and h-BN, the problems of high friction coefficient, insufficient wear resistance, and weak anti-wetting and adhesion ability of traditional ceramic materials and metal-based protective materials at high temperatures are solved. Thus, it can meet the long-term protection requirements of the heating surface of power plant boilers under the condition of co-firing high-alkali coal.

[0024] 6. The self-lubricating wear-resistant composite material of this invention is in powder form and can be processed into bulk material using a tablet press. Its molten salt contact angle is >150°, and its coefficient of friction is 0.02~0.3 within a temperature range of room temperature to 1000℃. Furthermore, this self-lubricating wear-resistant composite material exhibits good water dispersibility and can be used as a functional filler in water-based coating systems, thus showing broad application prospects in fields such as 3D printing, molten salt energy storage tanks, industrial kilns, metal smelting, and thermal power units.

[0025] 7. The preparation process of this invention is simple and controllable, with low requirements for production equipment, no need for special vacuum or inert atmosphere environment, low actual application cost, and easy to prepare and apply on a large scale. Attached Figure Description

[0026] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.

[0027] Figure 1 This is a schematic diagram of the structure of the WS2-h-BN self-lubricating wear-resistant composite material of superhydrophobic salt prepared in Example 1 of the present invention.

[0028] Figure 2 The friction coefficient at room temperature of the WS2-h-BN self-lubricating wear-resistant composite material of superhydrophobic salt prepared in Example 2 of the present invention.

[0029] Figure 3 The contact angle of the WS2-h-BN self-lubricating and wear-resistant composite material of superhydrophobic salt prepared in Example 3 of this invention with molten NaCl. Detailed Implementation

[0030] A superhydrophobic tungsten disulfide-h-BN self-lubricating and wear-resistant composite material is disclosed. This composite material has a two-dimensional composite "sandwich intercalation" structure and is prepared by hydroxyl modification of WS2 and h-BN, vacancy defect regulation, and covalent intercalation. The self-lubricating, wear-resistant, and superhydrophobic properties of this composite material are formed by the synergistic effect of low surface energy, weak van der Waals forces, and low coefficient of friction.

[0031] Among them, the contact angle of molten salt on the surface of the composite material is >150°, and the coefficient of friction is 0.02~0.3 in the temperature range of room temperature to 1000℃.

[0032] Molten salt is one or more of sodium chloride, sodium sulfate, sodium carbonate, and sodium bicarbonate, with a melting point range of 300~1000℃.

[0033] WS2 is a hexagonal plate-like tungsten sulfide with a particle size controlled at 0.5–1 μm and a specific surface area controlled at 62–98 cm². 2 / g, purity ≥99.9%; h-BN is hexagonal plate-like boron nitride with a particle size controlled at 25~50 μm and a density of 2.1~2.29 g / cm³. 3 The boron content is >43.6%.

[0034] A method for preparing a superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material includes the following steps: S1. WS2 powder and a hydroxyl modifier are sequentially added to an ultrapure aqueous solution at a mass ratio (g / g / g) of 0.3:0.01~0.1:1. The hydroxyl modifier is one of H2O2, NaOH, or PFDTS. The mixture is stirred at 800~1000 r / min for 12~24 h to obtain a hydroxylated modified WS2 solution. The WS2 hydroxylated modified solution is then vacuum filtered to obtain a hydroxylated modified WS2 precipitate. The precipitate is collected and dried in a drying oven at 90℃ for 10 h to obtain the hydroxylated modified WS2 powder.

[0035] S2 involves placing h-BN powder into a muffle furnace for high-temperature oxygen doping, with the mass ratio (g / g) of h-BN powder to WS2 powder being 1:0.6~0.75. The muffle furnace is heated at a rate of 3-5 °C / min, set at a temperature of 600-850 °C, and held for 1.5-2 h. After the muffle furnace cools naturally, the vacancy-defect oxygen-doped h-BN powder is collected. The vacancy-defect oxygen-doped h-BN powder and hydroxyl modifier are added sequentially to an ultrapure aqueous solution at a mass ratio (g / g / g) of 0.1:0.02-0.1:1. The solution is stirred at 800-1000 r / min for 12-24 h to obtain an h-BN hydroxylation-modified solution. The h-BN hydroxylation-modified solution is vacuum filtered to obtain a hydroxylation-modified h-BN precipitate. The precipitate is collected and dried in a drying oven at 70 °C for 16 h to obtain the hydroxylation-modified h-BN powder.

[0036] S3 involves sequentially adding hydroxylated modified WS2 powder, hydroxylated modified h-BN powder, and a covalent intercalation solvent to a ball mill jar at a mass ratio of 0.6–0.75:1:0.01 (g / g / g). The covalent intercalation solvent is one or both of APTES and KH560. Wet ball milling is then performed in a high-energy ball mill using anhydrous ethanol as the solvent. The milling speed is 800–1200 rpm, the ball-to-powder mass ratio (g / g) is 5:1, and the anhydrous ethanol to raw material mass ratio (g / g) is (1.5–2):1. The milling time is 24–36 h. After milling, a mixed powder is obtained. The mixed powder is then vacuum filtered and dried at 90°C for 2.5 h to obtain the WS2-h-BN self-lubricating wear-resistant composite material.

[0037] Example 1 A method for preparing a superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material includes the following steps: S1 Weigh 3g of WS2 powder, 1g of H2O2, and 10g of ultrapure aqueous solution into a beaker. The beaker is then sealed and placed on a magnetic stirrer, stirred at 1000 r / min for 24 h to obtain a WS2 hydroxylated modified solution. The WS2 hydroxylated modified solution is then vacuum filtered to obtain a hydroxylated modified WS2 precipitate. The precipitate is collected and dried in a vacuum drying oven at 90℃ for 10 h. After natural cooling, the hydroxylated modified WS2 powder is obtained.

[0038] S2. 5g of h-BN powder was placed into a corundum ceramic boat. Then, the corundum ceramic boat containing h-BN powder was transferred to a muffle furnace. The heating rate of the muffle furnace was set to 3℃ / min, the temperature was set to 600℃, and the holding time was 2 h. After natural cooling, the h-BN powder doped with vacancy defect oxygen was collected.

[0039] The vacancy-defect oxygen-doped h-BN powder and H2O2 were added sequentially to an ultrapure aqueous solution at a mass ratio (g / g / g) of 0.1:0.1:1. The beaker containing the resulting mixed solution was placed on a magnetic stirrer and stirred at 1000 r / min for 12 h to obtain a uniformly dispersed h-BN hydroxylated modified solution. The h-BN hydroxylated modified solution was vacuum filtered to obtain a hydroxylated modified h-BN precipitate. The precipitate was collected and dried in a drying oven at 70 °C for 16 h. After natural cooling, the hydroxylated modified h-BN powder was obtained.

[0040] S3: Hydroxylated modified WS2 powder, hydroxylated modified h-BN powder, and APTES covalent intercalation solvent were added sequentially to a ball mill jar at a mass ratio of 0.75:1:0.01 (g / g / g), and wet ball milling was performed in a high-energy ball mill. The solvent was anhydrous ethanol, the milling speed was 800 rpm, the ball-to-powder mass ratio (g / g) was 5:1, the anhydrous ethanol to raw material mass ratio (g / g) was 1.5:1, and the milling time was 36 h. After ball milling, a mixed powder was obtained. The mixed powder was vacuum filtered and dried at 90℃ for 2.5 h to obtain the WS2-h-BN self-lubricating wear-resistant composite material.

[0041] A schematic diagram of the structure of the WS2-h-BN self-lubricating wear-resistant composite material is shown below. Figure 1 As shown.

[0042] Example 2 A method for preparing a superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material includes the following steps: S1 Weigh 3g of WS2 powder, 0.1g of NaOH, and 10g of ultrapure aqueous solution into a beaker. The beaker is then sealed and placed on a magnetic stirrer, stirred at 800 rpm for 12 h to obtain a hydroxylated modified WS2 solution. The WS2 hydroxylated modified solution is then vacuum filtered to obtain a hydroxylated modified WS2 precipitate. The precipitate is collected and dried in a vacuum drying oven at 90℃ for 10 h. After natural cooling, the hydroxylated modified WS2 powder is obtained.

[0043] S2. 4g of h-BN powder was placed into a corundum ceramic boat. Then, the corundum ceramic boat containing h-BN powder was transferred to a muffle furnace. The heating rate of the muffle furnace was set to 4℃ / min, the temperature was set to 750℃, and the holding time was 1.5 h. After natural cooling, the h-BN powder doped with vacancy defect oxygen was collected.

[0044] The vacancy-defect oxygen-doped h-BN powder and NaOH were sequentially added to an ultrapure aqueous solution at a mass ratio (g / g / g) of 0.1:0.02:1. The beaker containing the resulting mixed solution was placed on a magnetic stirrer and stirred at 800 r / min for 24 h to obtain a uniformly dispersed h-BN hydroxylated modified solution. The h-BN hydroxylated modified solution was vacuum filtered to obtain a hydroxylated modified h-BN precipitate. The precipitate was collected and dried in a drying oven at 70 °C for 16 h. After natural cooling, the hydroxylated modified h-BN powder was obtained.

[0045] S3: Hydroxylated modified WS2 powder, hydroxylated modified h-BN powder, and APTES covalent intercalation solvent were sequentially added to a ball mill jar at a mass ratio of 0.6:1:0.01 (g / g / g), and wet ball milling was performed in a high-energy ball mill. The solvent was anhydrous ethanol, the milling speed was 1200 rpm, the ball-to-powder mass ratio (g / g) was 5:1, the anhydrous ethanol to raw material mass ratio (g / g) was 2:1, and the milling time was 24 h. After ball milling, a mixed powder was obtained. The mixed powder was vacuum filtered and dried at 90℃ for 2.5 h to obtain the WS2-h-BN self-lubricating wear-resistant composite material.

[0046] [Friction Performance Test] The WS2-h-BN self-lubricating wear-resistant composite material was placed in a tablet press, with a pressure of 15 MPa and a holding time of 10 min, to obtain a test sample with a diameter of 10 mm and a thickness of 2 mm. The coefficient of friction of the coating at room temperature and high temperature was tested using a high-temperature tribometer, with the reference standard being ASTM G133. The test conditions were reciprocating friction conditions, and the normal force was set to 5 N.

[0047] In this embodiment, the temperature was set to 30℃, the friction pair was Al2O3, the slip frequency was 1 Hz, and the test time was 700 s. The results are as follows: Figure 2 As shown, the average coefficient of friction of the test sample at room temperature is 0.243.

[0048] Example 3 A method for preparing a superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material includes the following steps: S1 Weigh 3g of WS2 powder, 0.5g of PFDTS, and 10g of ultrapure aqueous solution into a beaker. The beaker is then sealed and placed on a magnetic stirrer, stirred at 900 rpm for 18 h to obtain a WS2 hydroxylated modified solution. The WS2 hydroxylated modified solution is then vacuum filtered to obtain a hydroxylated modified WS2 precipitate. The precipitate is collected and dried in a vacuum drying oven at 90℃ for 10 h. After natural cooling, the hydroxylated modified WS2 powder is obtained.

[0049] S2. 4.5 g of h-BN powder was placed into a corundum ceramic boat. Then, the corundum ceramic boat containing h-BN powder was transferred to a muffle furnace, the heating rate of the muffle furnace was set to 5 °C / min, the temperature was set to 850 °C, and the holding time was 1.8 h. After natural cooling, the h-BN powder doped with vacancy defect oxygen was collected.

[0050] The vacancy-defect oxygen-doped h-BN powder and hydroxyl modifier were sequentially added to an ultrapure aqueous solution at a mass ratio (g / g / g) of 0.1:0.05:1. The beaker containing the resulting mixed solution was placed on a magnetic stirrer and stirred at 900 r / min for 18 h to obtain a uniformly dispersed h-BN hydroxylated modified solution. The h-BN hydroxylated modified solution was vacuum filtered to obtain a hydroxylated modified h-BN precipitate. The precipitate was collected and dried in a drying oven at 70 °C for 16 h. After natural cooling, the hydroxylated modified h-BN powder was obtained.

[0051] S3 involves adding hydroxylated modified WS2 powder, hydroxylated modified h-BN powder, and KH560 covalent intercalation solvent sequentially into a ball mill jar at a mass ratio of 0.7:1:0.01 (g / g / g). The covalent intercalation solvent is one or both of APTES and KH560. Wet ball milling is then performed in a high-energy ball mill using anhydrous ethanol as the solvent. The milling speed is 1000 rpm, the ball-to-powder mass ratio (g / g) is 5:1, the anhydrous ethanol to raw material mass ratio (g / g) is 1.8:1, and the milling time is 18 h. After milling, a mixed powder is obtained. The mixed powder is then vacuum filtered and dried at 90℃ for 2.5 h to obtain the WS2-h-BN self-lubricating wear-resistant composite material.

[0052] The WS2-h-BN self-lubricating wear-resistant composite material was placed in a tablet press, with a pressure of 15 MPa and a holding time of 10 min, to obtain a test sample with a diameter of 10 mm and a thickness of 2 mm.

[0053]

Molten NaCl Test

[0054] The test sample was placed at the center of the high-temperature wetting angle measuring instrument, and the high-speed camera was adjusted to ensure its outline was clearly visible. Then, coarse salt particles were placed symmetrically at the center of the test sample. Subsequently, a vacuum of 1×10⁻⁶ was applied. -3 The temperature was set at 850℃, with a heating rate of 10℃ / min and a holding time of 2 hours. When the temperature reached the set value, the melting state and contact angle of the molten NaCl were photographed. The results are as follows: Figure 3 As shown. The test results indicate that the contact angle of this test sample with molten NaCl is greater than 150°.

[0055] [Friction Coefficient Test] The high-temperature friction properties of the coatings obtained in Examples 1-3 were tested.

[0056] The coefficient of friction of the test specimens at high temperatures was tested using a high-temperature tribological testing machine, referencing ASTM G133. The test conditions were reciprocating friction, with a normal force of 5 N. The initial temperature was set at 30 °C, the temperature rise rate at 10 °C / min, and the target temperature ranges were set at 750 °C and 1000 °C. The specimens were held at the set temperature for 1 hour after reaching the set value, followed by reciprocating friction testing. The friction pair was Al₂O₃, the slip frequency was 1 Hz, and the test duration was 700 s. The results are shown in Table 1.

[0057] Table 1. Friction performance indicators of the materials prepared in Examples 1-3 at different temperature ranges. Test results show that the coefficient of friction of the WS2-h-BN self-lubricating wear-resistant composite material is 0.02~0.3 in the temperature range of room temperature to 1000℃. Combined with the material's superhydrophobic properties, this invention can provide application support for surface protection in high-temperature applications such as 3D printing, molten salt energy storage tanks, industrial kilns, metal smelting, and thermal power units.

Claims

1. A superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material, characterized in that: The composite material has a two-dimensional composite "sandwich intercalation" structure, which is prepared by hydroxyl modification of WS2 and h-BN, vacancy defect regulation and covalent intercalation.

2. The tungsten disulfide-h-BN self-lubricating wear-resistant composite material of superhydrophobic salt as described in claim 1, characterized in that: The contact angle of the molten salt on the surface of the composite material is >150°, and the coefficient of friction is 0.02~0.3 in the temperature range of room temperature to 1000℃.

3. The tungsten disulfide-h-BN self-lubricating wear-resistant composite material of superhydrophobic salt as described in claim 1, characterized in that: The molten salt is one or more of sodium chloride, sodium sulfate, sodium carbonate, and sodium bicarbonate, with a melting point range of 300~1000℃.

4. The tungsten disulfide-h-BN self-lubricating wear-resistant composite material of superhydrophobic salt as described in claim 1, characterized in that: The WS2 is a hexagonal plate-like tungsten sulfide with a particle size controlled at 0.5~1 μm and a specific surface area controlled at 62~98 cm². 2 / g, purity ≥99.9%; the h-BN is hexagonal plate-like hexagonal boron nitride with a particle size controlled at 25~50 μm and a density of 2.1~2.29 g / cm³. 3 The boron content is > 43.6%.

5. A method for preparing a superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material as described in any one of claims 1 to 4, comprising the following steps: S1. WS2 powder and hydroxyl modifier are sequentially added to an ultrapure aqueous solution in a mass ratio of 0.3:0.01~0.1:

1. The solution is stirred at 800~1000 r / min for 12~24 h to obtain a WS2 hydroxylated modified solution. The WS2 hydroxylated modified solution is then vacuum filtered and dried to obtain hydroxylated modified WS2 powder. S2. h-BN powder is placed in a muffle furnace for high-temperature oxygen doping. After the muffle furnace cools naturally, the vacancy-defect oxygen-doped h-BN powder is collected. The vacancy-defect oxygen-doped h-BN powder and hydroxyl modifier are added sequentially to an ultrapure aqueous solution in a mass ratio of 0.1:0.02~0.1:

1. The solution is stirred at 800~1000 r / min for 12~24 h to obtain an h-BN hydroxylation modified solution. The h-BN hydroxylation modified solution was vacuum filtered and dried to obtain hydroxylation modified h-BN powder. S3. The hydroxylated modified WS2 powder, the hydroxylated modified h-BN powder, and the covalent intercalation solvent are added sequentially to a ball mill jar at a mass ratio of 0.6~0.75:1:0.01, and wet ball milling is performed in a high-energy ball mill to obtain a mixed powder. The mixed powder is then vacuum filtered and dried to obtain the WS2-h-BN self-lubricating wear-resistant composite material.

6. The preparation method of the superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material as described in claim 5, characterized in that: The hydroxyl modifier in steps S1 and S2 refers to one of H2O2, NaOH, and PFDTS.

7. The method for preparing a superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material as described in claim 5, characterized in that: In step S2, the mass ratio of h-BN powder to WS2 powder is 1:0.6~0.

75.

8. The preparation method of the superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material as described in claim 5, characterized in that: In step S2, high-temperature oxygen doping refers to a heating rate of 3~5 ℃ / min for the muffle furnace, a set temperature of 600~850℃, and a holding time of 1.5~2 h.

9. The method for preparing a superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material as described in claim 5, characterized in that: The covalent intercalation solvent in step S3 is one or both of APTES and KH560.

10. The method for preparing a superhydrophobic tungsten disulfide-h-BN self-lubricating wear-resistant composite material as described in claim 5, characterized in that: The conditions for wet ball milling in step S3 are as follows: the solvent is anhydrous ethanol, the ball milling speed is 800~1200 rpm, the ball-to-material mass ratio is 5:1, the mass ratio of anhydrous ethanol to raw material is (1.5~2):1, and the ball milling time is 24~36 h.

Citation Information

Patent Citations

  • A graphite treatment method for barrier to molten salt and molten metal infiltration

    CN115050490B

  • Adhesive layer material resistant to molten salt thermal corrosion and preparation method thereof

    CN117286384B